Natural DYE extract from Ixora siamensis as light harvester for dye-sensitized solar cells with nanostructured TiO2 / Nur Amirah Mat Nor - Nur Amirah , Mat Nor (2019)
Research towards new natural dye sources along with eco-friendly and cost-effective technologies have greatly aided in various applications. Dye-sensitized solar cells (DSSCs) become more interesting since a huge variety of natural dyes from various sources can be used as light harvesting elements which provide the charge carriers. In this study, the natural dye has been extracted from Ixora siamensis or locally known as “jejarum” which is revealed to have the presence of anthocyanin compounds containing cyanidin-3-rutinoside, delphinidin glucoside and peonidin-3-glucoside. Response surface methodologies (RSM) were used to investigate the effect of extraction parameters and evaluate the optimized extraction conditions. The anthocyanin extraction from fruit pericarp of Ixora siamensis was performed by using acidified methanol in temperature between 30 and 80 ℃. The fruit pericarp of Ixora siamensis have been soaked for 60 to 180 min in acidified methanol with different trifluoroacetic acid (TFA) content between 0.5 to 3%. The optimized extraction parameter were 0.5% TFA, 119 min soaking time and 80 ℃ temperature. The anthocyanin extraction has been used as photosensitizer in DSSCs because anthocyanin compound has carbonyl or hydroxyl groups that can attach effectively to the surface of the porous TiO2 film. Dye-sensitized solar cells were fabricated by sandwiching the PAN-based gel polymer electrolytes between TiO2/dye photoanode and platinum (Pt) as the counter electrode. The morphology of the TiO2 also played important roles in achieving high power conversion efficiency. TiO2 electrospun materials have been produced via electrospinning technique in order to investigate the potential of these nanostructures, which will be used as metal oxide semiconductor in DSSCs application. The structures and morphology of the electrospun material have been characterized by FESEM and XRD analysis. The efficiency for DSSCs application using P25 TiO2 nanoparticle electrodes (D3) was (1.076  0.042)% when soaked in 3 wt.% dye solution. The composite electrode of TiO2 nanoparticle-nanorod (NPs-NRs) with inclusion of 10 wt.% NRs (CP1) have been fabricated and resulted in an increase of efficiency to (1.317  0.035)% when soaked in 3 wt.% dye solution. In order to increase the efficiency performance, two types of additives; chenodeoxycholic acid (CDCA) ferulic acid (FA) are used. On addition of 1 wt.% CDCA (C1), the efficiency slightly increased to (1.393  0.039)% with short current density, Jsc of (4.835  0.095) mA cm-2, open circuit voltage, Voc of (0.458  0.006) V and fill factor, FF of (0.629  0.010). On addition of 3 wt.% of FA (F3), the efficiency enhanced to (1.917  0.045)% with short circuit current density, Jsc of (6.178  0.128) mA cm-2, open circuit voltage, Voc of (0.473  0.009) V and fill factor, FF of (0.656  0.010). It has been shown in this work that addition of CDCA and FA to the anthocyanin solution improves the efficiency of the DSSCs.